Nursing and respect to professional autonomy in hospital environment: overprotection or negligence - Arango Bayer, Gloria Lucía (Avances en Enfermería, 2013)
The discourse on autonomy finds its place in modern times, in the acknowledgement of human dignity and the capacity that reasoning and will confer on a person for making free choices, for self-determining. But….why is it that we nurses – particularly in the hospital environment– are confronted with so many difficulties at the time of putting it into practice? Proposed in this essay are two of the major —albeit not the only— possible explanations to these difficulties. The first of them: lack of clarity in relation to the meaning and scope of the principle; the second: the consideration of the principles of autonomy and welfare as divergent regarding the history itself of the profession, where respect of autonomy might be seen as contrary to the duty that we are professionally bound to: the duty of caring for others. Based on these approaches, some recommendations are presented, particularly for education in nursing, which would imply incorporating in formation the bioethics discourse.